Literature Review Factors Affecting Leadership: Quality of Work, Work Effectiveness and Work Communication - Rajab, Muhammad (Dinasti International Journal of Economics, Finance & Accounting, 2021)
The literature review article on factors that influence Leadership: Work Quality, Work Effectiveness, and Work Communication is a scientific article that aims to build a research hypothesis on the influence between variables that it will use for further research, as well as within the scope of Human Resource Management. In this literature review article, the researcher uses the library research method by reviewing previous papers relevant to this research variable on online media such as Google Scholar and Mendeley and other online media. The results of this study are 1) Work Quality affects Leadership; 2) Work Effectiveness affects Leadership; and 3) Work Communication affects Leadership, apart from the three exogenous variables that affect the endogenous variables. There are many other factors, including 1) The quality of work affects Leadership; 2) Work Effectiveness affects Leadership; and 3) Work Communication affects Leadership.